Determinants of Firm Value: The Role of Corporate Social Responsibility as Moderation - Maulidya Al Afshana, Dida; Ika Prajawati, Maretha (Universitas Muhammadiyah Malang, 2024)
Purpose: Examine and offer empirical evidence on how financial decisions, namely investment decision, funding decision, and dividend policy affect firm value, with Corporate Social Responsibility (CSR) as a moderation. Methodology/approach: This study employs quantitative research methodology alongside Moderated Regression Analysis (MRA) method using SPSS analysis tool. Data used are financial reports and sustainability reports. Population for this research is manufacturing firms operating in primary consumer goods sector within beverage and processed food industry that are publicly listed on the Indonesia Stock Exchange (BEI) during period 2021 to 2023 with a total of 42 firms. Sampling involved purposive sampling, resulting in a sample of 6 firms. Findings: Results of this research reveal that investment decision and funding decision positively impact firm value significantly, whereas dividend policy doesn’t demonstrate any influence on firm value. CSR is unable to moderate the relationship between how investment decision, funding decision, and dividend policy on firm value. Practical implications: This research provides benefits for new knowledge in the field of management, especially financial management in the application of scientific studies related to investment decisions, funding decisions, dividend policies and company value and can be a guide and consideration for companies in making decisions so they can maximize company value. Originality/value: This research uses Corporate Social Responsibility (CSR) as a moderating variable which is measured by CSRDI.